2016
DOI: 10.1080/15384101.2016.1176657
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling molecular effects of ADAR1 overexpression in HEK293T cells by label-free quantitative proteomics

Abstract: ADAR1 is a double-stranded RNA (dsRNA) editing enzyme that specifically converts adenosine to inosine. ADAR1 is ubiquitously expressed in eukaryotes and participate in various cellular processes such as differentiation, proliferation and immune responses. We report here a new proteomics study of HEK293T cells with and without ADAR1 overexpression. The up-and down-regulated proteins by ADAR1 overexpression are identified by liquid chromatography-tandem mass spectrometry (LC-MS/MS) followed by label-free protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Notably, ADAR1 depletion in hESCs abrogates pluripotency and induces expression of transcripts that govern differentiation 47 . Conversely, enforced ADAR1 expression in a human embryonic kidney cell line (HEK293T) directly regulates the expression of more than 300 proteins involved in protein translation and cell cycle regulation 48 . Together, these studies suggest that the functional impact of changes in the RNA editome may be far-reaching, but this requires further investigation in the context of primary human cell types and tissue-specific stem cells.…”
Section: A-to-i Editing In Cscsmentioning
confidence: 99%
“…Notably, ADAR1 depletion in hESCs abrogates pluripotency and induces expression of transcripts that govern differentiation 47 . Conversely, enforced ADAR1 expression in a human embryonic kidney cell line (HEK293T) directly regulates the expression of more than 300 proteins involved in protein translation and cell cycle regulation 48 . Together, these studies suggest that the functional impact of changes in the RNA editome may be far-reaching, but this requires further investigation in the context of primary human cell types and tissue-specific stem cells.…”
Section: A-to-i Editing In Cscsmentioning
confidence: 99%
“…In total, the present study identified 5290 PGs in the proteome of HEK293T-D 2S R cells, allowing for comprehensive expression profiling. Guo et al, who tested the influence of overexpression of adenosine deaminase acting on RNA 1 (ADAR1) on the HEK293T proteome, found 1495 proteins in total in non-fractionated whole cell lysates 32 . Besides 1091 proteins that were identified in both studies, 4199 additional proteins were assigned by the present study, which also used non-fractionated whole cell lysates.…”
Section: Discussionmentioning
confidence: 99%
“…More than five random fields per well were captured at 200× magnification. Image-Pro Plus 6.0 software (IPP 6.0) was used to calculate the percentage of EdU-positive cells (identified by Apollo® 643 fluorescence) among all cells (identified by Hoechst 33,342 nucleus staining) 15…”
Section: Methodsmentioning
confidence: 99%